Efectos de la medida cautelar de prisión preventiva emitidas por jueces a procesados que pertenecen a las comunidades, nacionalidades y pueblos indígenas - Masaquiza Masaquiza, Soledad Maribel (2024)
This work referring to the effects of the precautionary measure of pre-trial detention issued by judges to defendants who belong to communities, nationalities and indigenous peoples, aims to analyze the application of pre-trial detention to individuals who belong to indigenous communities that violates the principle of interculturality, mixed approach, of a non-experimental nature with legal dogmatic and sociological scope. The methods of the theoretical level of knowledge used were analytical, synthetic, inductive, deductive and exegetical. The population interviewed were ten indigenous people who were prosecuted for criminal offenses and three prosecutors from the Ambato canton of Tungurahua province. It was concluded that when giving pre-trial detention to people who are members of indigenous communities, it violates the principle of interculturality, since cultural elements related to customs, ancestral practices, norms, procedures of the law of peoples, nationalities, communes and indigenous communities are not taken into account in order to apply the rights established in the Constitution and international instruments and art. 10 of ILO Convention 169.